2020
DOI: 10.1177/1756286420971895
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparity in long-term stroke recurrence and mortality in a rural population in the United States

Abstract: Background: Several studies suggest women may be disproportionately affected by poorer stroke outcomes than men. This study aims to investigate whether women have a higher risk of all-cause mortality and recurrence after an ischemic stroke than men in a rural population in central Pennsylvania, United States. Methods: We analyzed consecutive ischemic stroke patients captured in the Geisinger NeuroScience Ischemic Stroke research database from 2004 to 2019. Kaplan–Meier (KM) estimator curves stratified by gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
14
2
Order By: Relevance
“…An alternate explanation is that the mean age in POINT was relatively young, with a relatively low prevalence of high-risk conditions such as atrial fibrillation. [19][20][21] Additional prior studies on the association between sex and stroke recurrence include analyses of administrative claims data from a rural region of the United States 12 and for diabetic patients in Ontario, Canada. 13 Though these data were from narrowly defined populations and lacked granular clinical data, their findings were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternate explanation is that the mean age in POINT was relatively young, with a relatively low prevalence of high-risk conditions such as atrial fibrillation. [19][20][21] Additional prior studies on the association between sex and stroke recurrence include analyses of administrative claims data from a rural region of the United States 12 and for diabetic patients in Ontario, Canada. 13 Though these data were from narrowly defined populations and lacked granular clinical data, their findings were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,10 Whether these differences impact stroke recurrence risk has not been definitively assessed. Prior studies, which included a large proportion of stroke mimics 11 or used non-adjudicated administrative claims data, 12,13 did not find clear evidence of a sex difference in stroke recurrence.…”
Section: Introductionmentioning
confidence: 96%
“…The results of the ROSEsampled XGBoost model indicated that age, hypertension, and gender-in this specific cohort-were not significantly associated with 30-day readmission after ischemic stroke. We have also performed a detailed analysis of our Geisinger cohort and identified that sex was not an independent risk factor for allcause mortality and ischemic stroke recurrence (33). Finally, the identification of malnutrition provides potential new venues to improve secondary prevention and outcome (34).…”
Section: Clinical Features Highly Associated With 30-day Readmissionmentioning
confidence: 95%
“…GNSIS contains longitudinal clinical data for ischemic stroke patients compiled from various sources, including electronic health records data (EHR), social security death data, and quality data. The GNSIS database has been described in detail in previous studies [ 13 , 14 , 15 ]. The study was reviewed and approved by the Geisinger Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%